HARDWARE IMPLEMENTATION OF INTELLIGENT HOME ENERGY CONSERVATION SYSTEM WITH IoT PLATFORM - et al., J. Praveena (International Journal of Advanced Science and Technology, 2019)
Energy consumption has seen a tremendous rise since the dawn of Industrial revolution. One of the major characteristics of intelligent homes and energy management systems (EMS) is to integrate IOT ((Internet of things) and sustainable energy sources at the consumption premises. With advancement of Automation technology, today’s world prefers Automatic systems over manual systems. In this work, the outline, enactment and reliability of an embedded system using Arduino for energy management to a bright home incorporated with IOT. The proposed work initiates and controls the energy of an intelligent home. IOT is the new and emerging technology which connects the things through internet. In everyday object IOT is the most developing network to share the data from industrial machine to client services through wireless fidelity communication. IOT is a system that uses smart devices like data processing machine, tablets or mobile devices to control all roles and characteristics of smart homes automatically through internet. To achieve a better, higher utilization and optimization of energy flow a two way communication is developed to modify the load profile of the home. To simulate this load profile the paradigm of the proposed system was designed and tested by employing a controlled load bank.